Weariness for soul not to be too late (Confluenţe Bibliologice, 2012)
The author focuses on the meaning and importance of spiritual and moral education of each individual, which really is a cultivation of the spirit, which helps us to form a particular value of spiritual, ethical and aesthetic system.  In our aspiration for perfection we relate to God, divine being.